A case study of narcissistic pathology : an object relations perspective - Ivey, Gavin William (Rhodes University, Faculty of Humanities, Department of Psychology, 1989)
The case-study method of psychological research was applied to the brief psychodynamic therapy of a narcissistically disordered female patient. The aim of this research was to explore, clarify and explain certain diagnostic and psychodynamic anomalies to emerge in the course of treatment, using a conceptual framework derived from select psychoanalytic object relations theorists in the area of narcissistic pathology. The author, discovering that there was no diagnostic or explanatory object relations model adequate to the therapeutic data, formulated his own diagnostic category narcissistic neurosis and an eclectic object relations model in order to explain the anomolous research findings. Narcissistic neurosis was defined as a form of psychopathology in which a primarily neurotic character structure presents with a distinctly narcissistic profile. The narcissistic false self-structure serves the functional purpose of protecting the psyche from a repressed negative self-representation derived from a destructive bipolar self-object introject. The primary etiological factor to emerge was that of a narcissistic mother conditional affection and self-object target child necessitated adaptive whose insensitivity, relationship with the premature self-sufficiency and the defensive emergence of a narcissistic surface self-representation. It was proposed that narcissistic neurosis and narcissistic personality disorder are two discrete forms of pathology differing in terms of severity, psychodynamics, defensive structure, mode of object relating, therapeutic accessibility and prognosis. Assessment criteria were proposed in order to differentiate the two areas of narcissistic pathology and assess suitability for psychotherapeutic treatment. Positive treatment results in this case-study suggest that narcissistic neuroses may receive long-term benefit from short-term psychodynamic therapy.
Keywords: Narcissism; Narcissism -- Treatment